Factors Associated to the work Performance of Midwives in The Implementation on Stimulation, Early Detection and Intervention to Growth and Development of Infants and Pre-School Children (A Study on Midwives Working at Sidoarjo District Primary Healthcare - Hanik Machfudloh; Martha Irene Kartasurya; Dharminto Dharminto (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2014)
Rata - rata cakupan SDIDTK balita dan anak prasekolah pada Dinas Kesehatan Kabupaten Sidoarjo tahun 2008, 2009 berturut-turut adalah 61,52% 46,93% dan masih dibawah SPM tahun 2009 yaitu 80%. Penelitian ini bertujuan mengetahui faktor-faktor yang mempengaruhi kinerja bidan dalam pelaksanaan SDIDTK balita dan anak prasekolah di Puskesmas Kabupaten Sidoarjo. Jenis penelitian observasional analitik dengan pendekatan cross sectional. Populasi penelitian adalah seluruh bidan di Puskesmas Kabupaten Sidoarjo berjumlah 375 bidan. Subjek penelitian sejumlah 77 bidan dipilih secara proportional random sampling berdasarkan Puskesmas. Pengumpulan data dengan angket dan observasi. Variabel bebas adalah pengetahuan, sikap, motivasi, beban kerja, peralatan dan persepsi supervisi sedangkan variabel terikat adalah kinerja bidan dalam pelaksanaan SDIDTK balita dan anak prasekolah. Uji statistik menggunakan Chi-Square test dan Regresi Logistik Ganda. Hasil penelitian menunjukkan rerata umur Bidan 35 tahun dengan simpang baku 7,2 tahun. Seluruh subjek berpendidikan D III Kebidanan, dan 90,9% mempunyai status kepegawaian PNS. Rerata masa kerja 11,7 tahun dengan simpang baku 7,6. Bidan telah mendapatkan pelatihan SDIDTK dengan rerata 5,3 ± 3,2 tahun yang lalu. Sebagian besar bidan(59,7%) memiliki pengetahuan kurang, 62,3% sikap negatif, 57,1% motivasi kurang, 58,4% berpersepsi beban kerja berat, 57,1% peralatan kurang, 54,5% berpersepsi supervisi kurang, dan 54,5% mempunyai kinerja kurang. Ada hubungan positif antara pengetahuan, sikap, motivasi, peralatan dan persepsi supervisi dengan kinerja bidan. Ada hubungan negatif antara beban kerja dengan kinerja bidan. Kelengkapan peralatan, pengetahuan dan sikap berhubungan secara bersama-sama dengan kinerja bidan. Faktor yang paling berkaitan dengan kinerja bidan dalam pelaksanaan SDIDTK balita dan anak prasekolah adalah kelengkapan peralatan. Disimpulkan bahwa kinerja bidan dalam pelaksanaan SDIDTK masih kurang. Hal ini berkaitan dengan kelengkapan peralatan, pengetahuan dan sikap bidan terhadap pelaksanaan SDIDTK.The average of SDIDTK coverage of under-five and pre-school children in the work area of Sidoarjo district health office in 2008 and 2009 respectively was 61.52% and 46.93%. It was still below 2009 SPM (80%). Objective of this study was to identify factors affecting the work performance of midwives in the implementation of SDIDTK of under-five and pre-school children in the primary healthcare centers of Sidoarjo district. This was an observational-analytical study with cross sectional approach. Study population was all 375 midwives in the primary healthcare centers (puskesmas) in Sidoarjo district. Study subjects were 77 midwives who were selected using proportional random sampling method. Data collection was done using questionnaire and by conducting observation. Independent variables were knowledge, attitude, motivation, workload, instruments, and perception on supervision. Dependent variable was work performance of midwives in the implementation of SDIDTK of under-five and pre-school children. Chi-square test and multiple logistic regressions were applied in the data analysis. Results of the study showed that the average age of midwives was 35 years old with standard deviation of 7.2 years old. All subjects’ education level was D3 in midwifery; 90.9% were government civil servants (PNS). The average working period was 11.7 years with standard deviation of 7.6 years. Midwives had received SDIDTK training with the average of 5.3 ± 3.2 years ago. The majority of midwives had insufficient knowledge (59.7%), negative attitude (62.3%), low motivation (57.1%), heavy workload perception (58.4%), inadequate instruments (57.1%), inadequate supervision (54.5%), and inadequate work performance (54.5%). There was a positive association between midwives work performance and knowledge, attitude, motivation, instrument, and perception on supervision. There was a negative association between workload and midwives work performance. Completeness of instruments, knowledge, and attitude were jointly associated with the work performance of midwives. The most related factor to the work performance of midwives in the implementation of SDIDTK of under-five and pre-school children was the completeness of instruments. In conclusion, the work performance of midwives in the implementation of SDIDTK was still inadequate. This was related to the completeness of instruments, knowledge, and midwives attitude toward the implementation of SDIDTK.